Grounded Theory Model of Women's Managerial Competencies Based on Industrial Technological Innovations: A Case Study of Entrepreneurial Food Companies - Samadi , Masoumeh; Mohammadi, Mohammad; Hakimpour, Hossein; Rezaeifar, Hamid (Management Strategies and Engineering Sciences, 2024)
The aim of this study is to present a grounded theory model of women's managerial competencies based on industrial technological innovations (case study: entrepreneurial food companies). This research is exploratory in nature and qualitative in methodology. The statistical population of the study includes 15 women managers, deputies, and experts in the food industry, as well as distinguished entrepreneurship professors from universities. The sampling was conducted using snowball sampling. The data collection tool used in this study was a questionnaire focused on women’s management and technological innovation. Grounded theory was used to analyze the data. The indicators of negative societal attitudes toward women's management, patriarchy, and gender stereotypes, as well as the absence of women in political groups, were identified as intervening conditions in the presentation of the model for women’s managerial competencies in the food industry. The indicators of aligning abilities with assigned tasks, resolving conflicts between work and family, work experience, mastery over one’s profession, and updating one’s knowledge, awareness, and expertise were selected as strategies and actions in the presentation of the model for women’s managerial competencies in the food industry. The indicators of analytical and critical thinking, creative thinking, strategic thinking, systems thinking, general and specialized knowledge, research skills, presenting innovative and scientific ideas, adequate knowledge and expertise, work commitment, emotional intelligence, responsibility and accountability, self-esteem and self-confidence, self-awareness and insight, discipline, confidentiality, resolving interpersonal conflicts, receptiveness to criticism and recommendations, humility in behavior, understanding employee problems and aligning them with organizational goals, humanitarian and compassionate attitudes, identifying problems, evaluating solutions, and establishing good social relationships with other employees were selected as causal conditions in the presentation of the model for women’s managerial competencies in the food industry.